Risk Factors of Urinary Frequency Among Women Aged 60 and Older in Taiwan - Ching-Hung Hsieh; Wei-Chun Chang; Ming-I Hsu; Han-Sun Chiang; Shao-Tung Chang; Meng-Chih Lee; Maw-Sheng Lee; Kang-Ping Lu; Tsung-Hsien Su; Shu-Hsin Lee; Fu-Min Chen (Elsevier, 2010)
Objective: To assess the associated risk factors for daytime urinary frequency among Taiwanese women aged = 60 years. Materials and Methods: Daytime urinary frequency, defined by the International Continence Society, and its associated problems were evaluated, and medical history and sociodemographic variables were recorded. A total of 2,410 women were selected by a multistage random sampling method. The factors were assessed by frequency and Pearson's ?2 test using a significance level of < 0.05. Results: A total of 621 women of those initially selected in the study died before completion of this study. Face-to-face interviews with 1,521 women were completed, producing a response rate of 85.0% (1,521/1,789 women). The prevalence of daytime urinary frequency was significantly related to body mass index (p = 0.018), diabetes mellitus (p = 0.017), hypertension (p = 0.015), previous drug allergy (p = 0.003), smoking (p = 0.005), hormone therapy (p = 0.019), parity (p = 0.019), and urinary incontinence (p = 0.000). However, there was no association between urinary frequency and previous gynecologic surgery, hysterectomy, alcohol consumption, marital status, childbirth, and age of menopause. Conclusion: The results of this study showed a relatively high risk of urinary frequency development in patients with urinary incontinence, diabetes mellitus, hypertension, obesity, and smoking that are preventable, modifiable, or controllable. Better quality of health education for these women, drawing their attention to the associated factors, may have an impact on the prevalence of urinary frequency.